1999
DOI: 10.1002/(sici)1096-9071(199905)58:1<54::aid-jmv8>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of SDF-1 chemokine, CCR-5, and CCR-2 chemokine receptor gene alleles conferring resistance to human immunodeficiency virus type 1 and AIDS in Kuwaitis

Abstract: The frequencies of three mutations conferring resistance to HIV/AIDS were determined in a population sample of native Kuwaitis. The CCR2-641, SDF1-3'A, and CCR5-m303 mutations were detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) tests using restriction endonucleases Bsa BI, Msp I, and Hinc II, respectively. The frequency of the mutant alleles were: for CCR2-641, 0.1195 (95% CI 0.0801-0.1694); for SDF1-3'A, 0.2593 (95% CI 0.2024-0.3231), and for CCR5-m303, less than 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
4
38
1
Order By: Relevance
“…This could be because the sample-size (50 individuals) was small or because of miscegenation. Since previous studies (Voevodin et al 1999;Shieh et al1999;Wang et al 2003) have not detected the m303 allele in Asian populations we did not expect to find it in either the Waiampi or Tiriyó populations because they are of Asian descent, and this was indeed the case.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…This could be because the sample-size (50 individuals) was small or because of miscegenation. Since previous studies (Voevodin et al 1999;Shieh et al1999;Wang et al 2003) have not detected the m303 allele in Asian populations we did not expect to find it in either the Waiampi or Tiriyó populations because they are of Asian descent, and this was indeed the case.…”
mentioning
confidence: 69%
“…The mutant m303 allele was not identified in 200 Kuwaitis (Voevodin et al 1999), nor among 687 South Africans (Williamson et al 2000) or in seronegative but HIV-1 infected Chinese (Shieh et al1999;Wang et al 2003), although the m303 gene was detected at an allelic frequency of 0.007 in 145 Caucasians (Williamson et al 2000).…”
mentioning
confidence: 99%
“…The beta variant has a guanine to adenine (G→a) single nucleotide polymorphism at position 801 of the 3'-untranslated region of its gene (30)(31)(32). allele a is probably a target for cis-acting factors, capable of up-regulating the expression of SdF-1 protein (30,32,33). it has been suggested that homozygotes for SdF1-3'a (3'a/3'a) produce more SdF-1 than wild-type ones (3'G/3'G), an observation which is in need of confirmation (32,34,35).…”
Section: Introductionmentioning
confidence: 99%
“…allele a is probably a target for cis-acting factors, capable of up-regulating the expression of SdF-1 protein (30,32,33). it has been suggested that homozygotes for SdF1-3'a (3'a/3'a) produce more SdF-1 than wild-type ones (3'G/3'G), an observation which is in need of confirmation (32,34,35). This single nucleotide polymorphism of the SdF-1 gene has been investigated in type 1 diabetes and HiV-1 infection, and has been reported to be associated with an increased risk of non-Hodgkin's lymphoma in HiV-1 infected individuals (30,34,35).…”
Section: Introductionmentioning
confidence: 99%
“…The CCR5D32 genotype was determined by PCR with primers spanning the 32 bp deletion (Martinson et al, 1997). The SDF1-3'A and CCR2-64I mutations were detected by PCR with primers covering polymorphic sites, followed by MspI and BsaBI digestion, respectively, and restriction fragment length polymorphism (RFLP) analysis as described by Voevodin et al (1999).…”
mentioning
confidence: 99%